Revision of Neotropical species of Empidoidea (Diptera) described by Mario Bezzi. X. The species described in Apalocnemis Philippi (Brachystomatidae, Trichopezinae) - Rafael, J. A.; Sinclair, Bradley J. (Zootaxa, 2012)
Bezzi described two species in Apalocnemis Philippi, which at that time was placed in Empididae. This genus is presentlyassigned to Brachystomatidae, Trichopezinae. The type specimen of A. variegata Bezzi, 1905 is lost. Apalocnemis cingulata Bezzi, 1909 is redescribed and a lectotype designated based on a male specimen from Sicuani, Peru.